The Wave Effect Analysis Caused By Blasting Toward Highwall Slope Stability At Coal Mining, Pit 3000 Block 05 Sb 1, PT Trubaindo Coal Mining, Kutai Western District, East Kalimantan Province - Guntur Suryo Putro; Bambang Wisaksono; S Koesnaryo (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
PT Trubaindo Coal Mining (PT TCM) is a coal mining company located in West Kutai, East Kalimantan.Demolition of overburden layer is done by drilling and blasting can effect results primarily blastingground vibration for highwall slope stability. Controlled blasting activities undertaken in 3000 Pit Block05 using linedrill. Vibration measurement data obtained from the reading apparatus is not necessarilya factor affecting vibration highwall slope stability, but with the direction of propagation horizontalvibrations that cause the decrease highwall slope stability. The maximum horizontal accelerationarising from blasting activities as parameters that play a role in the stability of the slope obtained bylinking the PPA with the equation Amax = 0.5167 x PPA. Therefore, to determine the effect of groundvibration due to blasting for highwall slope stability modeling needs to be done cross-section A-A ', BB',C-C ', D-D' and E-E '. Results of prediction equations safety factor value of each cross-section asfollows: Section of A-A’, FK = 5,1489 amax 6 – 32,719 amax 5 + 79,933 amax 4 – 93,928 amax 3 + 54,189 amax 2 – 13,898 amax + 1,30852 Section of B-B’, FK = 0,4838 amax 6 – 3,0058 amax 5 + 7,0149 amax 4 – 7,6767 amax 3 + 4,4953 amax 2 – 2,4997 amax + 1,44549 Section of C-C’, FK = 1,2021 amax 6 – 7,4203 amax 5 + 16,907 amax 4 – 17,239 amax 3 + 8,0429 amax 2 – 2,8212 amax + 1,3628 Section of D-D’, FK = 5,279a amax 6 – 33,941 amax 5 + 84,105 amax 4 – 100,68 amax 3 + 59,648 amax 2 – 15,946 amax + 1,57907 Section of E-E’, FK = -1,9442 amax 6 + 11,453 amax 5 – 24,289 amax 4 + 20,677 amax 3 – 2,7313 amax 2 – 4,8741 amax + 1,65573The calculation results of critical maximum horizontal acceleration for every cross-section varies asthe follows: Section of A-A’, amax-critical = 0,007 g Section of B-B’, amax-critical = 0,118 g Section of C-C’, amax-critical = 0,062 g Section of D-D’, amax-critical = 0,025 g Section of E-E’, amax-critical = 0,09 gVariation is influenced by the thickness of the layer of top soil (top soil) and any cross-sectionalgeometry highwall slope.